Synthesis and Analgesic Activity of Some 2-[4-(Alkyl thioureido)phenylsulphonamido]-6-substituted benzothiazoles - Siddiqui, Nadeem; Alam, Mahfuz; A. Siddiqui, Anees (Asian Journal of Chemistry, 2016)
Series of sulphonamide derivatives (5a-i) were prepared by condensation of 2-(4-aminophenyl sulphonamido)-6-substituted benzothiazoles with alkyl isothiocyanates. The compound 5g with methoxy substitution showed maximum analgesic activity in the series. Highly significant results were also observed with compound 5b, 5f and 5h whereas other compounds of the series showed a decrease in analgesic activity.